Postmodern and poststructural approaches to nursing research - Cheek, Julianne; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
This title offers a pluralistic perspective on the patient experience and patient care.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nursing -- Research; Postmodernism; Poststructuralism; Electronic books